PENGARUH TINGKAT LEVERAGE TERHADAP AGRESIVITAS PAJAK MELALUI RETURN ON ASSET (ROA) SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Happy Bernada Simatupang; Harlyn L Siagian (Universitas Muhammadiyah Jember, 2021)
ABSTRACTThe purpose of this study is to analyze whether the level of leverage has an effect on tax aggressiveness through Return on Assets as a mediating variable. The sample consisted of 75 samples and used a purposive sampling technique for 25 companies, namely by collecting data on the Food and Beverage Sub-Sector companies listed on the Indonesia Stock Exchange in 2017-2019. This study uses data analysis techniques, namely multiple linear regression analysis and mediation regression processed in SPSS 22. Therefore the results of the study show that partially the variable leverage, ROA has an effect on tax aggressiveness. However, by testing the Mediation Variable, Leverage does not have a significant effect on tax aggressiveness and only ROA as a mediating variable has a significant value on Tax Aggressiveness.Keywords : Leverage Rate, Tax Aggressiveness and Return On Asset